2022
DOI: 10.2460/ajvr.21.11.0177
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and ex vivo pharmacodynamics of oral firocoxib administration in New Zealand White rabbits (Oryctolagus cuniculus)

Abstract: OBJECTIVE To examine the pharmacokinetics and ex vivo pharmacodynamics of oral firocoxib administration in New Zealand White rabbits (Oryctolagus cuniculus). ANIMALS 6 healthy New Zealand White rabbits. PROCEDURES Pharmacokinetics were determined from plasma concentrations measured via ultra performance liquid chromatography-tandem mass spectrometry after oral administration of firocoxib at a dose of 3.74 to 4.20 mg/kg. Pharmacokinetic analysis was performed using non compartmental methods. Pharmacodynamic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The individual variation in C max between the rabbits in the study was also wide (0.12-0.47 μg/ml for oral administration and 4.24-9.10 μg/ml for subcutaneous administration). This warrants consideration when choosing between this medication and other non-steroidal anti-inflammatory medications with less variability in C max to potentially achieve more consistent results in clinical use (Gardhouse et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The individual variation in C max between the rabbits in the study was also wide (0.12-0.47 μg/ml for oral administration and 4.24-9.10 μg/ml for subcutaneous administration). This warrants consideration when choosing between this medication and other non-steroidal anti-inflammatory medications with less variability in C max to potentially achieve more consistent results in clinical use (Gardhouse et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Robenacoxib analysis was conducted by adapting methods for firocoxib in rabbits (Gardhouse et al, 2022). Briefly, frozen samples and standards (robenacoxib and robenacoxib‐d3 (Sigma‐Aldrich)) were thawed at room temperature and rigorously vortexed once completely thawed.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The only pharmacokinetic studies of NSAIDs in rabbits currently are for meloxicam and firicoxib, and both were found to have a short half-life and therefore require a frequent dosing interval. [4][5][6] Previous pharmacokinetic studies of mavacoxib in mammalian species have been limited to the domestic dog, 2,3 where one study showed that a single 2 mg/kg PO dose reached therapeutic plasma concentrations for the management of osteoarthritis. 3 Mavacoxib has also been studied in a limited number of avian species, including the cockatiel (Nymphicus hollandicus), 7,8 the flamingo (Phoenicopterus ruber ruber), 9 and the African grey parrot (Psittacus erithacus).…”
mentioning
confidence: 99%